Domain Restriction in Generic Statements. Issue 7 (8th August 2020) - Clifton, Charles; Frazier, Lyn
ABSTRACT: Domain restriction is a pervasive if often neglected part of discourse comprehension. Speakers and authors implicitly limit the domain of discourse of quantifiers (e.g., everyone ) and noun phrases (e.g., the girls ). Our previous research shows that an initial temporal or locative prepositional phrase (PP), which introduces a topic situation, is the preferred context for interpreting the domain of subject noun phrases in the same sentence or a subsequent sentence. In this research, the sentences and minidiscourses were about concrete nongeneric situations. The present article reports three experiments designed to explore domain restriction in generic statements. Experiment 1 shows that indefinite determiners and the presence of a modal ( would ) favor generic interpretations. In Experiments 2 and 3 a sentence initial (vs. sentence final) PP increased interpretation of the subject as being restricted to the topic situation as well as increasing the frequency of generic interpretations. We propose that in sentences with modals ( would ) the initial PP acts as the antecedent of a conditional. Furthermore, based on differences in responses depending on whether the genericity of the subject or the temporal restriction on the subject are posed, we suggest that domain restriction is an inference from the representation constructed during discourse comprehension while a decision about genericity is a part of core sentence interpretation.